Lviv urban green on the example of selected objects - Dudkiewicz, Margot; Durlak, Wojciech; Szmagara, Mariusz; Bevz, Mykola (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
Lviv is the largest city in western Ukraine. The authors discuss three public parks located in the city center, presenting their historical outlines, compositions and spatial layout as well as small architectural objects. These include Ivan Franko Park, Central Cultural and Recreation Park for them. Bohdan Chmielnicki and Stryjski Park. These public city park locations have an interesting history of origins and transformations, recreational and recreational functions, valuable dendroflora and birdlife. There are convenient paths and walking trails for walking in the parks, with small architectural objects (rubbish bins, benches, lanterns), as well as playgrounds, gazebos and monuments.